Electrochemical studies of copper, copper-aluminium and copper-aluminium-silver alloys: Impedance results in 0.5M NaCl - Benedetti, Assis Vicente [UNESP]; Sumodjo, P. T. A.; Nobe, K.; Cabot, P. L.; Proud, W. G. (Elsevier B.V., 1995)
The electrochemical behaviour of Cu, Cu-Al and Cu-Al-Ag alloys in aqueous solutions of NaCl (0.5 M, pH = 3.00) was studied by means of voltammetric methods and electrochemical impedance spectroscopy. The surfaces were examined by SEM and EDX analysis. Cu-Al-Ag alloy shows a potentiodynamic behaviour similar to that of the pure copper electrode while the Cu-Al alloy presents some minor differences. In the active dissolution region the electrodes suffer pitting corrosion and in the other potential regions there are the formation of a passivant film with composition depending on the potential. The impedance responses of the electrodes are discussed. An electrodissolution mechanism is proposed and the effect of the alloying elements upon the impedance response and polarisation curves is explained. The main effects are due to the production of copper and silver chlorides and aluminium oxides/ hydroxides at the corroding interface. The addition of Al or (Al + Ag) increases the corrosion resistance of pure copper. © 1995.
Keywords: Alloy oxidation; Copper-based alloys; Impedance studies; Potentiodynamic; Alloying elements; Corrosion; Electrochemical electrodes; Electrochemistry; Oxidation; Pitting; Scanning electron microscopy; Sodium chloride; Solutions; Spectroscopy; Surfaces; X ray diffraction analysis; Alloy oxidation; Electrochemical impedance spectroscopy; Potentiodynamic; Voltammetric methods; Copper alloys